2019
DOI: 10.1186/s12889-019-6658-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of routine diagnostic work-up for tuberculosis in lung clinics in Yogyakarta, Indonesia: a cohort study

Abstract: Background Establishing a correct diagnosis is challenging. We aimed to investigate the sensitivity and specificity of routine tuberculosis (TB) diagnostic work-up in lung clinics in Indonesia, a country with the third highest TB burden and the second highest gap between notifications of TB cases and the best estimate of incident cases in the world. Methods In the lung clinics of the Province of Yogyakarta, Indonesia, we recruited all consecutive patients with symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In addition, follow-up should be employed to ensure that the diagnosis made was correct. A previous study has shown that follow-up could help to cover the weakness of culture and improve its accuracy [55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, follow-up should be employed to ensure that the diagnosis made was correct. A previous study has shown that follow-up could help to cover the weakness of culture and improve its accuracy [55].…”
Section: Discussionmentioning
confidence: 99%
“…The existing tests have high sensitivity, such as culture and PCR [1], or very high specificity, such as Gene Xpert [57], or moderate sensitivity, such as sputum smear microscopy [1,55]. However, these highly sensitive tests are not point-of-care, are sputum-dependent, prone to laboratory fallacy, and need trained laboratory personnel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture though gold standard for TB but single spot sputum culture is challenging; low quality of sputum samples and laboratory errors may jeopardize both sensitivity and specificity. The CRS that diagnoses TB based on comprehensive results of clinical symptoms, bacteriological examinations, CXR, and follow-up, could address these drawbacks of culture [15,19].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, their efficacy was found to be relatively poor when compared with other more modern methods, which utilise molecular or immunological techniques. The diagnostic flaws of these methods are often attributed to the effect of the human error in interpretation of the results [41]. To overcome this, several companies are developing computational algorithms and the use of Artificial Intelligence (AI) [42] to better interpret chest X-ray results (discussed later).…”
Section: Direct Culture and Observationmentioning
confidence: 99%